Customer Switching Behavior of Patimban Port Service Users - Bunardi, Gunawan; Sugiharti, Endang; Sonny, Imam (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2025)
Tanjung Priok Port has been experiencing cargo congestion and a slowdown in the flow of goods, resulting in bottlenecks and congestion around the port. Patimban Port as a national strategic project is expected to synergize with Tanjung Priok Port and offers a solution to this problem. However, customer switching from Tanjung Priok Port to Patimban Port remains low. This research aims to analyze the performance of port operational services, competitiveness between ports, and customer switching behavior from Tanjung Priok Port to Patimban Port. Qualitative research is adopted for this study, with data collection performed through literature study, observation and interviews. This study utilizes qualitative descriptive analysis method and two round Delphi method for data analysis. The research results demonstrate that the operational service performance of Tanjung Priok Port and Patimban Port is satisfactory. In addition, Tanjung Priok Port boasts superior competitiveness compared to Patimban Port. Competitive advantages offered by Tanjung Priok Port include facilities and capacity, easy road access, and port digitalization, meanwhile, Patimban Port offers advantages in terms of loading and unloading speed and more competitive rates. The switching of customers from Tanjung Priok Port is relatively not optimal due to service quality, loading and unloading speed, road accessibility and logistics costs. Policy stimulus and promotional strategies are therefore necessary to encourage customer switching behavior.